Research on the measurement and spatio-temporal evolution of marine new-quality productivity in China - Sha, Xiujuan; Tang, Huimin; Wang, Yuting (Frontiers in Marine Science, 2025)
With the deepening development of the new round of technological revolution, marine new quality productive forces (MNQPF), as a key driver for promoting the high-quality development of China's marine economy, exhibit significant regional disparities in coastal areas. These disparities hold critical implications for formulating scientifically grounded regional development strategies. Based on the three constituent elements of Marxist productive forces, this study employs the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) entropy method, Gini coefficient, and kernel density estimation to analyze the spatial-temporal evolution of MNQPF levels across China's coastal provinces using panel data from 2012 to 2021. The findings reveal:(1) China's MNQPF has shown an upward trend, yet its overall level remains relatively low;(2) Regional imbalances persist, with the Eastern Marine Economic Circle outperforming the Southern and Northern counterparts. Regional disparities primarily stem from inter-regional differences and super-variable density;(3) Spatial heterogeneity characterizes MNQPF development, manifesting as "balanced growth in central regions vs. uneven development in northern and southern areas." In this regard, relevant discussion recommendations are put forward: (1) The Eastern Marine Economic Circle should leverage technological spillover effects to extend high-end marine industries northward to the Bohai Rim Economic Circle and southward to the Beibu Gulf Economic Zone;(2) The Northern Marine Economic Circle should advance green transformation of "marine + heavy industry" through port-economic belt construction under integrated land-sea development strategies;(3) The Southern Marine Economic Circle ought to enhance cross-border marine cooperation by capitalizing on its role as a "Belt and Road" hub, while strengthening Guangdong's radiating influence on neighboring provinces.